Linguagem matemática: elemento de mediação no ensino e na aprendizagem de conteúdos matemáticos nos anos finais do ensino fundamental - GONSAGA, Suelen Sacramento (2023)
The mathematical language is a very relevant tool in the construction of mathematical knowledge. The complicacies faced by students in front of the complexity in the process of write and understanding can damage their relationship with the mathematical discipline. In this perspective, the present work aims to analyze how teachers understand the role of language in teaching and learning of mathematics in elementary school. The theoretical foundation that supports this study is based on the theories of different theorists who discuss the theme. For the proper development of the research with a qualitative approach the field research was carried out using as data collection instrument an electronic questionnaire applied to teachers working in the final years of elementary school. In general terms, it is understood that communication and language are essential for human beings and that mathematical language is a key element for understanding this important area of knowledge just as it is important educators aware of his role of mediators in the teaching and learning of mathematical content, make interventions and discuss with the student’s possible mistakes in the language effectively contributing to the improvement of understanding of mathematical concepts.